Battery diaphragm and preparation method thereof

By using ceramic slurry coating on the battery separator, combined with ionic liquid-modified Elostone tube and hot pressing leveling technology, the problems of easy shedding and poor mechanical properties of the traditional coating are solved, and the stability of the separator is improved. Lithium ion transfer efficiency extends the service life of the battery.

CN119275490AActive Publication Date: 2025-01-07HUBEI XIANCHUANG TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411407681.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The traditional battery separator coating is prone to fall off and has poor mechanical properties, resulting in short circuits and deterioration of battery performance, and is unable to effectively regulate lithium ion transfer behavior.

Method used

Using ceramic slurry coating, including solvents, adhesives and ionic liquid modified Elosite tubes, through physical crosslinking and ion exchange treatment, a slurry with uniform dispersion of nanoparticles is formed and coated on the nonwoven film. , and hot pressing and leveling are carried out to enhance the structural stability and mechanical properties of the coating.

Benefits of technology

It improves the puncture resistance and cycle stability of the diaphragm, enhances the migration ability of lithium ions, weakens the concentration polarization phenomenon, inhibits the growth of lithium dendrites, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275490A_ABST
    Figure CN119275490A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and discloses a battery diaphragm and a preparation method thereof. The battery diaphragm comprises a non-woven fabric membrane, the outer wall surface of the non-woven fabric membrane is coated with a ceramic slurry coating, and the ceramic slurry coating comprises a solvent, an adhesive and an ionic liquid modified halloysite tube. The halloysite tube modified by the ionic liquid is used for preparing the slurry, so that the nano particles can be uniformly dispersed in a polymer adhesive, and the problem that the nano particles are easy to aggregate is avoided. Due to the entanglement effect of organic chains on the peripheries of the nano particles and polymer adhesive chain segments, the structural stability and mechanical performance of the coating can be greatly improved, and the puncture-resistant strength of the diaphragm is improved. Meanwhile, the quaternary ammonium salt contained in the modified halloysite tube can also generate an adsorption effect on anions in the electrolyte, so that the transmission behavior of lithium ions is improved, the transference number of the lithium ions is increased, the concentration polarization phenomenon is weakened, the growth of lithium dendrites is inhibited, and the cycle life of a corresponding battery is further prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery separator and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles and energy storage, power lithium-ion battery technology has gradually become a research hotspot, which has put forward higher requirements on various components of the battery. The diaphragm is located between the positive and negative electrodes. Although it does not participate in the electrochemical reaction, it plays a role in isolating the positive and negative electrodes and allowing lithium ions to pass quickly, thus determining the charging and discharging and safety performance of the battery.

[0003] Non-woven fabric separators have the advantages of low cost and high porosity, and can achieve high temperature resistance through raw material selection, becoming the development trend of power lithium battery separators in the future. However, the non-woven fabric membrane formed by the accumulation of randomly oriented fibers has problems such as large and uneven pore size and poor mechanical properties. It is necessary to optimize the pore size and mechanical properties through appropriate means before it can be used as a lithium-ion battery separator. Otherwise, direct use will cause battery short circuit. Introducing a slurry prepared by mixing adhesives such as polyvinylidene fluoride and nanoparticles into the surface of non-woven fabrics is a common method for optimizing the pore size of the separator.

[0004] However, this traditional coating still has the following problems: under the long-term swelling of the electrolyte, the coating is easy to fall off, resulting in the occurrence of micro-short circuits in the battery and the decline of battery performance; the introduction of traditional coatings has limited improvement in the mechanical properties of non-woven membranes, which is not conducive to the inhibition of lithium dendrites and the stability of battery performance; and lacks the regulation of lithium ion transfer behavior. In summary, traditional coatings are easy to fall off and have poor mechanical properties. Summary of the invention

[0005] The main purpose of the present invention is to provide a battery separator and a preparation method thereof, aiming to solve the problem that traditional coatings are easy to fall off and have poor mechanical properties.

[0006] To achieve the above objectives, the present invention provides a battery separator, comprising a non-woven membrane, wherein a ceramic slurry coating is coated on the outer wall surface of the non-woven membrane, wherein the components of the ceramic slurry coating include a solvent, an adhesive and an ionic liquid-modified halloysite tube.

[0007] In one embodiment, the mass concentration of the adhesive is in the range of 5%-15%;

[0008] The mass concentration of the ionic liquid modified halloysite tubes ranges from 0.5% to 4.5%.

[0009] In one embodiment, the solvent is one or two of acetone, N,N-dimethylformamide or N,N-dimethylacetamide.

[0010] In one embodiment, the adhesive is one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene or polytetrafluoroethylene.

[0011] The present invention also provides a method for preparing a battery separator, which is characterized by comprising the following steps:

[0012] Dispersing the binder and the ionic liquid-modified halloysite tubes in a solvent and stirring them uniformly to obtain a physically cross-linked ceramic slurry;

[0013] Applying the ceramic slurry to the surface of the non-woven membrane;

[0014] The nonwoven fabric membrane is dried to obtain a nonwoven fabric-based composite separator to form the battery separator.

[0015] In one embodiment, the method for preparing the ionic liquid modified halloysite tube comprises:

[0016] The surface of the halloysite tube was grafted with dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride;

[0017] Performing ion exchange on the grafted halloysite tube using sodium salt of α-sulfo-ω-nonylphenoxy polyoxyethylene ether to obtain the ionic liquid-modified halloysite tube;

[0018] Wherein, the feeding ratio of the halloysite tube, the dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and the α-sulfo-ω-nonylphenoxypolyoxyethylene ether sodium salt is 1:2-5:1-3.

[0019] In one embodiment, the coating method of coating the ceramic slurry onto the surface of the non-woven fabric membrane includes any one of immersion coating, blade coating, cast coating or roller coating.

[0020] In one embodiment, the drying method of the nonwoven fabric membrane in the drying process includes any one of vacuum drying and air drying.

[0021] In one embodiment, after the non-woven fabric membrane is dried, the method further comprises:

[0022] The nonwoven membrane is flattened by hot pressing.

[0023] The present invention provides a battery separator, wherein the ionic liquid-modified halloysite tube is used for slurry preparation, and the uniform dispersion of nanoparticles in a polymer adhesive can be achieved, thereby avoiding the problem of easy aggregation of nanoparticles and weak interface action. At the same time, the structural stability and mechanical properties of the coating can be greatly improved through the entanglement effect of the organic chain of the nanoparticle periphery and the polymer adhesive chain segment, which can not only solve the problem of easy shedding of the coating during long-term circulation, but also improve the puncture resistance of the separator, thereby improving the long-term circulation stability of the separator. The ionic liquid-modified halloysite tube used in the present invention, the quaternary ammonium salt contained in the tube can produce an adsorption effect on the anions in the electrolyte, thereby improving the transfer behavior of lithium ions, increasing the lithium ion migration number, weakening the concentration polarization phenomenon and inhibiting the growth of lithium dendrites, thereby further improving the cycle life of the corresponding battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 1 is a SEM image of the diaphragm prepared in Example 2 of the present invention and Comparative Example 1;

[0025] Figure 2 1 is the stress-strain curve of the diaphragm prepared in Example 2 of the present invention and Comparative Example 1;

[0026] Figure 3 is the chronoamperometric curve and lithium ion migration number of the separator prepared in Example 2 of the present invention (the inset is the interfacial impedance spectrum before and after battery polarization);

[0027] Figure 4 It is the chronoamperometric curve and lithium ion migration number of the diaphragm prepared in Comparative Example 1 of the present invention (the inset is the interfacial impedance spectrum before and after battery polarization);

[0028] Figure 5 It is the cycle stability curve of the battery assembled with the diaphragms prepared in Example 2 of the present invention and Comparative Example 1.

[0029] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0032] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0033] Provided is a battery separator, comprising a non-woven fabric membrane, wherein a ceramic slurry coating is coated on the outer wall surface of the non-woven fabric membrane, wherein the components of the ceramic slurry coating include a solvent, an adhesive and an ionic liquid-modified halloysite tube.

[0034] In the battery separator provided by the present invention, the ionic liquid-modified halloysite tube is used for slurry preparation, which can realize the uniform dispersion of nanoparticles in the polymer adhesive, avoiding the problem of easy aggregation of nanoparticles and weak interface effect. At the same time, the structural stability and mechanical properties of the coating can be greatly improved through the entanglement effect of the organic chain of the nanoparticle periphery and the polymer adhesive chain segment, which can not only solve the problem of easy detachment of the coating during long-term circulation, but also improve the puncture resistance of the separator, thereby improving the long-term circulation stability of the separator. The ionic liquid-modified halloysite tube used in the present invention contains quaternary ammonium salts that can produce adsorption effects on anions in the electrolyte, thereby improving the transfer behavior of lithium ions, increasing the number of lithium ion migration, reducing the concentration polarization phenomenon and inhibiting the growth of lithium dendrites, thereby further improving the cycle life of the corresponding battery.

[0035] Furthermore, the mass concentration of the adhesive is in the range of 5%-15%; the mass concentration of the ionic liquid-modified halloysite tube is in the range of 0.5%-4.5%.

[0036] In another aspect, the solvent is one or both of acetone, N,N-dimethylformamide or N,N-dimethylacetamide.

[0037] On the other hand, the adhesive is one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene or polytetrafluoroethylene.

[0038] Based on the above-mentioned battery separator, the present invention also provides a method for preparing the battery separator, comprising the following steps:

[0039] S1, dispersing the binder and the ionic liquid-modified halloysite tubes in a solvent and stirring them evenly to obtain a physically cross-linked ceramic slurry;

[0040] S2, coating the ceramic slurry onto the surface of the non-woven membrane;

[0041] S3, drying the non-woven fabric membrane to obtain a non-woven fabric-based composite separator to form the battery separator.

[0042] Furthermore, the preparation method of the ionic liquid modified halloysite tube comprises:

[0043] S01, grafting on the surface of halloysite tube by dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride;

[0044] S02, performing ion exchange on the grafted halloysite tube using sodium salt of α-sulfo-ω-nonylphenoxy polyoxyethylene ether to obtain the ionic liquid-modified halloysite tube;

[0045] Wherein, the feeding ratio of the halloysite tube, the dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and the α-sulfo-ω-nonylphenoxypolyoxyethylene ether sodium salt is 1:2-5:1-3.

[0046] Specifically, the coating method of coating the ceramic slurry onto the surface of the non-woven fabric membrane includes any one of immersion coating, blade coating, cast coating or roller coating.

[0047] On the other hand, the drying method in the drying treatment of the nonwoven fabric membrane includes any one of vacuum drying and air blowing drying.

[0048] Furthermore, after the non-woven fabric membrane is dried, the method further comprises:

[0049] The nonwoven membrane is flattened by hot pressing.

[0050] It should be noted that the hot pressing and leveling temperature is 60-120°C and the pressure is 5-30Mpa.

[0051] Example 1

[0052] (1) Preparation of physically cross-linked ceramic slurry

[0053] The adhesive polyvinylidene fluoride and the ionic liquid modified halloysite tube are dissolved in DMF (N,N-dimethylformamide), stirred evenly, and a physically cross-linked ceramic slurry is obtained.

[0054] Wherein, in the ceramic coating slurry, the mass concentration of the adhesive is in the range of 5%, and the mass concentration of the ionic liquid modified halloysite tube is 0.5%.

[0055] The ionic liquid modified halloysite tube is obtained by grafting dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (DC5700) on the surface of the nanotube and subsequently exchanging ions of α-sulfo-ω-nonylphenoxypolyoxyethylene ether sodium salt (NPEP), wherein the feed ratio of halloysite tube, DC5700 and NPEP is 1:2:1.

[0056] (2) Preparation of non-woven fabric-based composite membrane

[0057] The ceramic slurry prepared in (1) was coated onto the surface of the PP non-woven fabric membrane by a dip coating method, dried at 60°C, and flattened by hot pressing at a pressure of 10 MPa and a temperature of 60°C to obtain a non-woven fabric-based composite diaphragm.

[0058] Example 2

[0059] (1) Preparation of physically cross-linked ceramic slurry

[0060] The adhesive polyvinylidene fluoride-hexafluoropropylene and the ionic liquid modified halloysite tube were dissolved in a mixed solvent of DMF and acetone (ratio of 10:1), and stirred evenly to obtain a physically cross-linked ceramic slurry.

[0061] Wherein, in the ceramic coating slurry, the mass concentration of the adhesive is in the range of 10%, and the mass concentration of the ionic liquid modified halloysite tube is in the range of 2%.

[0062] The ionic liquid modified halloysite tube is obtained by grafting dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (DC5700) on the surface of the nanotube and subsequently exchanging α-sulfo-ω-nonylphenoxypolyoxyethylene ether sodium salt (NPEP) with the ion, wherein the feed ratio of the halloysite tube, DC5700 and NPEP is 1:4:2.

[0063] (2) Preparation of non-woven fabric-based composite membrane

[0064] The ceramic slurry prepared in (1) was coated onto the surface of the PET non-woven fabric membrane by a blade coating method, dried at 80°C, and flattened by hot pressing at a pressure of 20 MPa and a temperature of 80°C to obtain a non-woven fabric-based composite diaphragm.

[0065] Example 3

[0066] (1) Preparation of physically cross-linked ceramic slurry

[0067] The adhesive poly(diylidene fluoride)-trichloroethylene and the ionic liquid-modified halloysite tube are dissolved in DMF and stirred evenly to obtain a physically cross-linked ceramic slurry.

[0068] Wherein, in the ceramic coating slurry, the mass concentration of the adhesive is in the range of 15%, and the mass concentration of the ionic liquid modified halloysite tube is 4.5%.

[0069] The ionic liquid modified halloysite tube is obtained by grafting dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (DC5700) on the surface of the nanotube and subsequently exchanging ions with sodium salt of α-sulfo-ω-nonylphenoxypolyoxyethylene ether (NPEP), wherein the feed ratio of the halloysite tube, DC5700 and NPEP is 1:5:3.

[0070] (2) Preparation of non-woven fabric-based composite membrane

[0071] The ceramic slurry prepared in (1) was coated onto the surface of the PPS non-woven membrane by roller coating, dried at 100° C., and flattened by hot pressing at a pressure of 25 MPa and a temperature of 100° C. to obtain a non-woven composite diaphragm.

[0072] Based on the above-mentioned battery separator, the present invention provides a comparative example of the prior art

[0073] Comparative Example 1

[0074] (1) Preparation of slurry

[0075] The adhesive polyvinylidene fluoride and halloysite tube were dissolved in DMF and stirred evenly to obtain a coating slurry.

[0076] Wherein, in the ceramic coating slurry, the mass concentration of the adhesive is in the range of 10%, and the mass concentration of the halloysite tube is in the range of 2%.

[0077] (2) Preparation of non-woven fabric-based composite membrane

[0078] The slurry prepared in (1) was coated onto the surface of the PET non-woven fabric membrane by a dip coating method, dried at 80° C., and flattened by hot pressing at a pressure of 20 MPa and a temperature of 80° C. to obtain a non-woven fabric-based composite diaphragm C.

[0079] Performance Testing

[0080] The diaphragms prepared in Example 2 of the present invention and Comparative Example 1 were photographed using a scanning electron microscope. Figure 1 (Left) is a SEM image of the diaphragm prepared in Example 2 of the present invention, Figure 1 (Right) is a SEM image of the surface of the diaphragm of comparative example 1 of the present invention. The use of ionic liquid-modified halloysite tubes to prepare slurry can greatly reduce the aggregation of nanoparticles in the matrix. At the same time, the introduction of organic segments on the surface of the halloysite tubes is conducive to the regulation of the polymer matrix segments in the solvent volatilization pore-forming process, which can hatch more abundant pores and is conducive to the adsorption and storage of the electrolyte.

[0081] The mechanical properties of Example 2 of the present invention and Comparative Example 1 were tested, wherein the length and width of the sample strip were 4 mm×15 mm, and the tensile rate during the test was 10 mm / min. Figure 2 2 is a stress-strain curve diagram of Example 2 of the present invention and Comparative Example 1. The diaphragm prepared in Example 2 shows a relatively high tensile strength of about 15 MPa, which is much higher than the tensile strength of the diaphragm prepared in Comparative Example 1. This is mainly due to the effective physical entanglement between the polymer segments in the polymer adhesive and the organic segments on the surface of the halloysite tube, thereby improving the cohesion and tensile strength of the coating. This interaction will help the coating to maintain structural stability during the long-term swelling process of the electrolyte and will not easily fall off from the substrate surface, thereby ensuring the electrochemical performance during the battery cycle.

[0082] The membranes prepared in Example 2 of the present invention and Comparative Example 1 were assembled into simulated batteries with lithium sheets as positive and negative electrodes, and the curve of current change over time was detected by an electrochemical workstation under a bias voltage of 10 mV. In addition, the electrochemical impedance spectroscopy test was performed on the battery before and after polarization. Combining the test results of the two, the lithium ion migration number of the membrane was calculated according to the following formula:

[0083]

[0084] Where: I 0 is the initial current obtained by chronoamperometry; I s is the steady-state current obtained by chronoamperometry; R 0 is the interface impedance at the initial moment obtained by EIS; R s is the interfacial impedance at the steady state obtained by EIS; ΔV is the voltage applied by the chronoamperometry, which is 10 mV. Figure 3 and Figure 4 The chronoamperometric curves and lithium ion migration numbers of the diaphragms prepared in Example 2 and Comparative Example 1 are shown respectively. The lithium ion migration number of the diaphragm prepared in Example 2 is 0.51, which is much higher than that of the diaphragm prepared in Comparative Example 1 (0.31). This is mainly due to the presence of four-season ammonium salt functional groups in the surface organic chains of the halloysite tubes, which can adsorb anions in the electrolyte, thereby promoting the ability of lithium ions to carry charges during battery operation, thereby increasing the migration number of lithium ions. This will help to reduce concentration polarization during battery operation, homogenize the distribution of lithium ions, and inhibit the growth of lithium dendrites.

[0085] The diaphragms prepared in Example 2 of the present invention and Comparative Example 1 were assembled into button batteries with lithium iron phosphate as the positive electrode and lithium sheet as the negative electrode in a glove box filled with argon. The lithium iron phosphate positive electrode was obtained by coating a slurry formed by adhesive polyvinylidene fluoride, acetylene black, and lithium iron phosphate (mass ratio of 1:1:8) on aluminum foil. The battery was charged and discharged 100 times at a set rate of 0.5C / 0.5C. Figure 5 The battery cycle stability curves of Example 2 of the present invention and Comparative Example 1 show that the diaphragm prepared in Example 2 of the present invention can provide more stable cycle performance for the battery. After the battery is charged and discharged 100 times, the battery performance retention rate is 98.5%. However, the cycle performance curve of the diaphragm prepared in Comparative Example 1 shows a significant downward trend. After the battery is charged and discharged 100 times, the battery performance retention rate is only 81.3%. This is mainly due to the effective physical entanglement between the polymer chain segments of the adhesive and the organic chains on the surface of the halloysite tube, which enhances the structural stability of the coating and its ability to resist electrolyte swelling, reduces the risk of coating shedding, and thus ensures the battery's charge and discharge performance during the cycle.

[0086] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A battery separator, characterized in that: The invention comprises a non-woven fabric membrane, the outer wall surface of which is coated with a ceramic slurry coating, wherein the components of the ceramic slurry coating include a solvent, an adhesive and an ionic liquid-modified halloysite tube.

2. The battery separator according to claim 1, characterized in that: The mass concentration of the adhesive is in the range of 5% to 15%; The mass concentration of the ionic liquid modified halloysite tubes ranges from 0.5% to 4.5%.

3. The battery separator according to claim 1, characterized in that: The solvent is one or two of acetone, N,N-dimethylformamide or N,N-dimethylacetamide.

4. The battery separator according to claim 1, characterized in that: The adhesive is one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene or polytetrafluoroethylene.

5. A method for preparing a battery separator, for preparing the battery separator according to any one of claims 1 to 4, characterized in that: The following steps are involved: Dispersing the binder and the ionic liquid-modified halloysite tubes in a solvent and stirring them uniformly to obtain a physically cross-linked ceramic slurry; Applying the ceramic slurry to the surface of the non-woven membrane; The nonwoven fabric membrane is dried to obtain a nonwoven fabric-based composite separator to form the battery separator.

6. The method for preparing a battery separator according to claim 5, characterized in that: The preparation method of the ionic liquid modified halloysite tube comprises: The surface of the halloysite tube was grafted with dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride; Performing ion exchange on the grafted halloysite tube using sodium salt of α-sulfo-ω-nonylphenoxy polyoxyethylene ether to obtain the ionic liquid-modified halloysite tube; Wherein, the feeding ratio of the halloysite tube, the dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and the α-sulfo-ω-nonylphenoxypolyoxyethylene ether sodium salt is 1:2-5:1-3.

7. The method for preparing a battery separator according to claim 5, characterized in that: The coating method of coating the ceramic slurry onto the surface of the non-woven fabric membrane includes any one of immersion coating, blade coating, cast coating or roller coating.

8. The method for preparing a battery separator according to claim 5, characterized in that: The drying method in the drying treatment of the nonwoven fabric membrane includes any one of vacuum drying and air blowing drying.

9. The method for preparing a battery separator according to claim 5, characterized in that: After the non-woven fabric membrane is dried, the method further comprises: The nonwoven membrane is flattened by hot pressing.

Citation Information

Patent Citations

  • Lithium ion battery, diaphragm and preparation method thereof

    CN108807813A

  • Lithium ion secondary battery

    JP2014060123A

  • Disposable electrodes based on nanoclay composites

    WO2022115080A1